Deep Breathing Relaxation Technique reduces Anxiety and Back Pain in third trimester pregnant women - Anita, Sari; Komariah, Nurul (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Anxiety and back pain in the third trimester of pregnancy are common discomforts in pregnant women. This occurs because of physiological and psychological changes in pregnant women before the birth process which can disrupt life and have a negative impact on pregnant women and fetuses. An effort to reduce anxiety and back pain in third trimester pregnant women is to use deep breathing relaxation techniques. The research method was carried out using descriptive analytical methods with a case study approach. The respondents were 1 pregnant woman in the third trimester who received continuous care from the third trimester of pregnancy until delivery from 29 November 2023 to 17 December 2023 at PMB Rabiah, Palembang city. The research instrument used was the SOAP midwifery care guide. Data was obtained through interviews, observation, documentation and literature study. The application process was carried out for 18 days and the results showed a change in reducing anxiety and back pain after applying this deep breathing relaxation technique so that the mother could undergo the birth process safely, without problems and complications. Conclusion: The use of deep breathing relaxation techniques has been proven to be able to reduce complaints of anxiety and back pain in third trimester pregnant women.